2020
DOI: 10.1016/j.jocd.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of High-Resolution Peripheral Quantitative Computed Tomography (HR-pQCT) in Patients with Suspected Scaphoid Fractures

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Due to its thin cortex and the fine trabecular network motion might have a different impact on image quality. Moreover, the subjectivity when classifying the bone into grade 1 to grade 5 seems higher for the scaphoid than for the radius and tibia (7).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Due to its thin cortex and the fine trabecular network motion might have a different impact on image quality. Moreover, the subjectivity when classifying the bone into grade 1 to grade 5 seems higher for the scaphoid than for the radius and tibia (7).…”
Section: Introductionmentioning
confidence: 96%
“…The CT also has a high specificity but a lower sensitivity; however, it is often preferred to the MRI as it is cheaper and more readily available (1,4,5). High-resolution peripheral quantitative computed tomography (HR-pQCT) represents an innovative option in detecting scaphoid fractures (6)(7)(8). Since the first results have only recently been published, its use is not yet widely established in this field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we found that HR-pQCT is a feasible and reliable technique for scaphoid fracture diagnosis 29 , with "almost perfect" interobserver agreement (Fleiss kappa, 0.91) according to the guidelines by Landis and Koch 35 . In the present Fig.…”
Section: Discussionmentioning
confidence: 89%
“…The development of high-resolution peripheral quantitative CT (HR-pQCT), a novel high-resolution and lowradiation-dose technique, allows for the assessment of cortical and trabecular bone microarchitecture at the distal parts of the radius and tibia 25,26 . Recent research has shown that studying the fracture-healing process of stable distal radial fractures 27,28 and scanning the scaphoid bone in patients with a clinically suspected scaphoid fracture are feasible with HR-pQCT 29 . We hypothesized that the use of HR-pQCT for patients with a clinically suspected scaphoid fracture would improve scaphoid fracture detection when compared with conventional CT in the clinical setting.…”
mentioning
confidence: 99%